Dignitaries visiting the Igorrote Village, Alaska Yukon Pacific Exposition, Seattle, 1909. - Nowell, Frank H., 1864-1950 (1909)
On verso of image: Igorotte Chief, on left, Director General Nadeau, in center and Governor General James F. Smith, of the Philippines, on the right. Photo taken in Igorrote Village at the Alaska-Yukon-Pacific Exposition. PH Coll 727.712 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number